QRIS-Based Zakat Management Strategy in Realizing Sustainable Development Goals - Osamah Naufal Rahman (Program Studi Manajemen Zakat dan Wakaf, 2026)
Non-cash zakat based on QRIS is an activity based on the current situation. The author would like to invite readers to understand the strategy in conducting QRIS zakat transactions in realising the values of Sustainable Development, reading the opportunities and challenges therein to achieve justice for humanity. The research method used is a qualitative approach with a literature review, which provides research results that the indicators of sustainable development goals (SDGs) in the QRIS non-cash zakat management strategy include: SDG 9 (industry, innovation, and infrastructure) and SDG 10 (reducing inequality), which provide appropriate and broader solutions for the community in accessing payment systems with inclusive and adaptive technological means. SDG 16 (strong, transparent, and accountable institutions) and SDG 17 (partnerships for the goals) support SDG 4 (quality education) and SDG 10 (reducing inequality) in the context of equitable access to information. To realise these indicators, it is necessary to pay attention to the strategy of managing non-cash QRIS zakat by developing digitalisation in all sectors, strengthening technological infrastructure in zakat institutions, strengthening digital literacy and human resource development, and integrated multi-sector collaboration in zakat digitalization.